Press coverage of HIV/AIDS in Northern Nigeria: a study of daily trust - Muhammad Hamid, Adamu; Tamam, Ezhar (Universiti Putra Malaysia, 2018)
Africa south of Sahara is still bearing more than half of the world’s HIV/AIDS burden. Because medical science has been unable to offer anything more than ways or methods of turning it from a fatal into a chronic condition, much emphasis and attention shifted to its prevention. The Mass Media has played a central role in that direction. Evidence of media reportage on HIV/ AIDS in countries with high prevalence rates like Nigeria, becomes worthwhile to ensure there is adequate dosage of media ‘vaccination’ against the disease.. In scoring the press in health priorities (particularly HIV/AIDS) against the backdrop of prescriptions of Development Media Theory in developing countries like Nigeria, this study attempts to investigate the major consistent newspaper in northern Nigeria, the Daily Trust, on its coverage of HIV/AIDS. The study content analyzed the newspaper to depict how the coverage of the disease is given priority in the region. Specific objectives of the study are to identify the Daily Trust’s major sources of news on HIV/AIDS, identify how the types of HIV/AIDS, news are covered in the newspaper, identify the major HIV/AIDS themes of the news stories, and determine the prominence the newspaper gives to HIV/AIDS news. The study covers the newspaper issues published over three years from 2013-2015 and the first half of 2016, from which 170 stories were studied: news stories, features and editorials. Data was analyzed using descriptive statistics. Hypothesized relationships between pairs of key content categories were tested and Pearson Chi Square value was significant between Source of HIV/AIDS story and HIV/AIDS story treatment, between Coverage of HIV/AIDS Major Themes and HIV/AIDS Story Presentation Taste, and between HIV/AIDS Source of Story and Geographic Focus of HIV/AIDS story. Findings also reveal that all HIV/AIDS stories were printed in the inside pages and none made front page headlines. There was also a shift from publishing grim HIV/AIDS figures to stories of hope and care for people living with HIV/AIDS. Most of the HIV/AIDS stories studied focused on urban centers and had no illustrations. It is therefore concluded that despite the importance of the disease which poses a challenge to development, HIV/AIDS is not given adequate coverage and attention by the press in Northern Nigeria.